A study in familial hypercholesterolemia suggests reduced methylomic plasticity in men with coronary artery disease. (February 2015) - Guay, Simon-Pierre; Brisson, Diane; Mathieu, Patrick; Bossé, Yohan; Gaudet, Daniel; Bouchard, Luigi
Aim: To assess whether DNA methylation is associated with coronary artery disease (CAD).Materials & methods: An epigenome-wide analysis has been performed on leucocytes from familial hypercholesterolemic (FH) men with (n = 6) or without CAD (n = 6). The results were replicated in an extended sample of FH men (n = 61) and in non-FH men (n = 100) for two of the top differentially methylated loci.Results: FH men with CAD had significantly more hypomethylated and hypermethylated loci and showed less DNA methylation level variability compared with men without CAD (p < 0.001). Moreover, COL14A1 and MMP9 DNA methylation levels were associated with CAD, age of onset of CAD or CAD risk factors.Conclusion: These results suggest that epigenome-wide changes are associated with CAD occurrence in men.